Sirolimus for the Treatment of Juvenile Polyposis in Childhood - Martin‐Masot, Rafael; Cardelo Autero, Nerea; Ortiz Pérez, María PIlar; Torcuato-Rubio, Encarnación; Vázquez Pedreño, Luis; Gallego Fernández, Carmen; Blasco Alonso, Javier; Navas-López, Víctor Manuel (Wolters Kluwer Health, 2021)
Juvenile polyposis syndrome (JPS) is a rare disease with an autosomal dominant inheritance pattern characterized by the development of multiple hamartomatous polyps in the gastrointestinal tract. The most frequent signs and symptoms are recurrent abdominal pain, rectal bleeding, anemia, and iron deficiency. The treatment of JPS is symptomatic, requiring serial endoscopic polypectomies or intestinal resections in the most severe cases. We describe the clinical case of a patient with JPS with a childhood juvenile polyposis phenotype because of a mutation on the SMAD4 gene, who received treatment with sirolimus successfully.
Keywords: Intestinos - Enfermedades; Juvenile Polyposis; Sirolimus